2001
DOI: 10.3758/bf03200498
|View full text |Cite
|
Sign up to set email alerts
|

Postcoincidence trajectory duration affects motion event perception

Abstract: In a two-dimensional display, identical visual targets moving toward and across each other with equal, constant speed can be perceived either to reverse their motion directions at the coincidence point (bouncing percept) or to stream through one another (streaming percept). Although there is a strong tendency to perceive the streaming percept, various factors have been reported to induce the bouncing percept, such as a sound or a visual flash at the moment of the visual target coincidence. By changing duration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
47
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 41 publications
3
47
0
1
Order By: Relevance
“…Sekuler, Sekuler, and Lau (1997) found that the perception of bouncing became dominant when a transient sound was presented at the coincidence of moving objects (hereafter, we will simply refer to this as at coincidence). They suggested that auditory signals at coincidence might be utilized to interpret an ambiguous streaming/bouncing display when combined with a visual signal; their results have been replicated and supported in later studies (Bushara et al, 2003;Scheier, Lewkowics, & Shimojo, 2003;Watanabe & Shimojo, 2001a, 2001b. Recently, suggested that multimodal attention might be involved in the perception of streaming/bouncing displays; multimodal transient signals, such as auditory tones and tactile vibrations, at coincidence reliably increased the perception of bouncing.…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…Sekuler, Sekuler, and Lau (1997) found that the perception of bouncing became dominant when a transient sound was presented at the coincidence of moving objects (hereafter, we will simply refer to this as at coincidence). They suggested that auditory signals at coincidence might be utilized to interpret an ambiguous streaming/bouncing display when combined with a visual signal; their results have been replicated and supported in later studies (Bushara et al, 2003;Scheier, Lewkowics, & Shimojo, 2003;Watanabe & Shimojo, 2001a, 2001b. Recently, suggested that multimodal attention might be involved in the perception of streaming/bouncing displays; multimodal transient signals, such as auditory tones and tactile vibrations, at coincidence reliably increased the perception of bouncing.…”
mentioning
confidence: 65%
“…In previous studies, a transient auditory signal at co- Time incidence biased the perception toward bouncing (Sekuler et al, 1997;Watanabe & Shimojo, 2001a, 2001b, as did distraction of visual attention (Burns & Zanker, 2000;Watanabe & Shimojo, 1998). However, in these previous studies, since a uniform geometric object was used as the moving object, it was unclear how the motion integration mechanism interacted with the modulation of attention.…”
Section: Discussionmentioning
confidence: 92%
“…Such conditions caused an object moving along a single continuous trajectory to appear to move along first one and then another, different trajectory. Recently, several researchers have implemented Metzger's stimuli as two identical discs that move smoothly across a computer display on opposed, intersecting paths (Bertenthal, Banton, & Bradbury, 1993;Sekuler & Sekuler, 1999;Watanabe & Shimojo, 2001a). The discs' momentary coincidence on the display sets up a perceptual ambiguity: the discs can either appear to pass through one another ("streaming"), or appear to collide and bounce off one another ("bouncing").…”
Section: Introductionmentioning
confidence: 99%
“…Prior to test sessions, our chimpanzees experienced equal numbers of unambiguous streaming and bouncing displays in training trials. However, in the natural world, a plausible assumption is that an object moving in one direction continues to move in that direction (Hall-Haro, Johnson, Price, Vance, & Kiorpes, 2008;Spelke, 1994), and any bouncing event is accidental (K. Watanabe & Shimojo, 2001a). This is consistent with the tendency of our visual system to interpret bistable ambiguous visual information, such as a stream/bounce display, as unidirectional movement (Anstis & Ramachandran, 1987;Bertenthal et al, 1993).…”
Section: Discussionmentioning
confidence: 56%
“…Previous studies have identified multiple factors that can alternate stream/bounce perception (Bertenthal et al, 1993;Grassi & Casco, 2009;Kawabe & Miura, 2006;A. B. Sekuler & R. Sekuler, 1999;K. Watanabe & Shimojo, 2001a, 2001b, and determining a single mechanism that would fully explain the vulnerability of streaming perception in chimpanzees is difficult.…”
Section: Discussionmentioning
confidence: 99%